The Extended Cell Panel Assay Characterizes the Relationship of Prion Strains RML, 79A, and 139A and Reveals Conversion of 139A to 79A-Like Prions in Cell Culture - Oelschlegel, Anja M. (American Society for Microbiology, 2012)
Three commonly used isolates of murine prions, 79A, 139A, and RML, were derived from the so-called Chandler isolate, which was obtained by propagating prions from scrapie-infected goat brain in mice. RML is widely believed to be identical with 139A; however, using the extended cell panel assay (ECPA), we here show that 139A and RML isolates are distinct, while 79A and RML could not be distinguished. We undertook to clone 79A and 139A prions by endpoint dilution in murine neuroblastoma-derived PK1 cells. Cloned 79A prions, when returned to mouse brain, were unchanged and indistinguishable from RML by ECPA. However, 139A-derived clones, when returned to brain, yielded prions distinct from 139A and similar to 79A and RML. Thus, when 139A prions were transferred to PK1 cells, 79A/RML-like prions, either present as a minor component in the brain 139A population or generated by mutation in the cells, were selected and, after being returned to brain, were the major if not only component of the population.